Left neglect dyslexia: Perseveration and reading error types. (August 2016) - Ronchi, Roberta; Algeri, Lorella; Chiapella, Laura; Gallucci, Marcello; Spada, Maria Simonetta; Vallar, Giuseppe
Abstract: Right-brain-damaged patients may show a reading disorder termed neglect dyslexia . Patients with left neglect dyslexia omit letters on the left-hand-side (the beginning, when reading left-to-right) part of the letter string, substitute them with other letters, and add letters to the left of the string. The aim of this study was to investigate the pattern of association, if any, between error types in patients with left neglect dyslexia and recurrent perseveration (a productive visuo-motor deficit characterized by addition of marks) in target cancellation. Specifically, we aimed at assessing whether different productive symptoms (relative to the reading and the visuo-motor domains) could be associated in patients with left spatial neglect. Fifty-four right-brain-damaged patients took part in the study: 50 out of the 54 patients showed left spatial neglect, with 27 of them also exhibiting left neglect dyslexia. Neglect dyslexic patients who showed perseveration produced mainly substitution neglect errors in reading. Conversely, omissions were the prevailing reading error pattern in neglect dyslexic patients without perseveration. Addition reading errors were much infrequent. Different functional pathological mechanisms may underlie omission and substitution reading errors committed by right-brain-damaged patients with left neglect dyslexia. One such mechanism, involving the defective stopping of inappropriate responses, may contribute to both recurrent perseveration in target cancellation, and substitution errors in reading. Productive pathological phenomena, together with deficits of spatial attention to events taking place on the left-hand-side of space, shape the manifestations of neglect dyslexia, and, more generally, of spatial neglect. Highlights: Neglect dyslexic patients with perseveration make more substitutions than omissions. Patients with no recurrent perseveration make more omission reading errors. Response inhibition deficits may underlie perseveration and substitution errors. Omission and substitution neglect paralexias are two independent disorders.